Failure analysis and mechanical behaviour of A60 steel bollards used in port infrastructure - El Kouifat, Mohammed Khalil; Zniker, Houcine; Feddal, Ikram; Ouaki, Bennaceur (Zielona Góra: Uniwersytet Zielonogórski)
The failure mechanisms and mechanical properties of bollards present significant risks in port and maritime engineering thereby calling for a thorough investigation into these aspects. This study highlights the significance of elements like tensile strength shear stress and service loads while examining the difficulties related to metal bollard failures.
Keywords: bollard failure; A60 steel bollard; mechanical behaviour; numerical simulation; von Mises stress